واقع تبني المسؤولية الاجتماعية في التسويق دراسة ميدانية في شركة جود للصناعات الغذائية - قاسم, سامر; وحود, نور (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف البحث إلى دراسة واقع تبني شركة جود للصناعات الغذائية لأبعاد المسؤولية الاجتماعية في التسويق, وذلك في المجالات الآتية: التعبئة والتغليف, والتوزيع المادي, والترويج, والتعامل مع حالة الامتياز. اعتمد البحث المنهج الوصفي الإحصائي, وتمّ تطوير استبانه لجمع البيانات الأولية عن مفردات عينة البحث, والبالغ عددها (123) من العاملين المسؤولين عن تسويق وتوزيع وترويج وتعبئة وتغليف المنتجات الغذائية في الشركة محل الدراسة, حيث تمّ توزيع الاستبانات عليهم واسترد (118) استبانة كاملة وبنسبة استجابة بلغت (95.93%). وكان من أهم نتائج البحث:1- تتبنى شركة جود للصناعات الغذائية بعد المسؤولية الاجتماعية في التسويق, والمتعلق بالتعبئة والتغليف بدرجة عالية, وبأهمية نسبية بلغت (78.384%).2- تتبنى شركة جود للصناعات الغذائية بعد المسؤولية الاجتماعية في التسويق, والمتعلق بالتوزيع المادي بدرجة عالية, وبأهمية نسبية بلغت (77.288%).3- تتبنى شركة جود للصناعات الغذائية بعد المسؤولية الاجتماعية في التسويق, والمتعلق بالترويج بدرجة عالية, وبأهمية نسبية بلغت (69.152%).4- تتبنى شركة جود للصناعات الغذائية بعد المسؤولية الاجتماعية في التسويق, والمتعلق بالتعامل مع حالة الامتياز بدرجة عالية, وبأهمية نسبية بلغت (77.458%).The research studies the current state and policy of the Joud company as an example of the resultant impact of the food industry adopting for social responsibility in marketing: packaging, physical distribution, promotion and dealing with the case of concession. The research adopts the descriptive method and develops a questionnaire for collecting the preliminary data comprising the research samples. This questionnaire has been handed to be filled by a staff of (123) employees with responsibilities covering marketing, distribution, promotion and packaging. The fully answered questionnaires count to 118 leading to a response rate of (95.93%). The most important search results are represented in:1- Joud company for food industries adopt the social responsibility in marketing related to packaging with a high degree and with a relativity importance reached (78.384%).2- Joud company for food industries adopt the social responsibility in distribution related to packaging with a high degree and with a relativity importance reached (77.288%).3- Joud company for food industries adopt the social responsibility in promotion related to packaging with a high degree and with a relativity importance reached (69.152%).4- Joud company for food industries adopt the social responsibility in dealing with the case of concession related to packaging with a high degree and with a relativity importance reached (77.458)%.